Conglomerates on the rise again? A cross-regional study on the impact of the 2008–2009 financial crisis on the diversification discount - Rudolph, Christin; Schwetzler, Bernhard (Journal of Corporate Finance, 2013)
This paper investigates how the 2008–2009 financial crisis affected the value of diversification in different regions of the world, thereby emphasizing the role of the institutional context. We show that the effect of the credit crunch upon the diversification discount varied with the regions' level of capital market maturity and legal environment. In developed Asia Pacific, the British Isles, and North America, we find that the discount on conglomerates fell significantly during the crisis years; however, in Continental Europe – the region possessing the least developed capital markets and lowest legal investor protection in our sample – the impact of the financial meltdown upon the relative value of diversified firms was insignificant. Our study provides additional evidence on factors influencing the relative costs and benefits of diversified firms and highlights in particular the importance of accounting for different institutional settings.